p-COUMARATES OF BETULA PENDULA (BETULACEAE) VEGETATIVE BUDS SESQUITERPENE ALCOHOLS - Dmitriy Nikolaevich Vedernikov; Elizaveta Mihailovna Ipanova (Химия растительного сырья, 2020)
The composition of coumarates sesquiterpene alcohols of Betula pendula Roth. birch vegetative buds was determined. Fraction was isolated from buds extract by preparative liquid chromatography. The extract was isolated by sequential extraction of an alcoholic extract of the buds with methyl tert-butyl ether. The new sesquiterpene derivatives were first detected in the birch vegetative buds. The structure of 6-hydroxyisocaryophyllene [(1R,4Z,6R,9S)-8-methylene-11,11-dimethylbicyclo[7.2.0]undec-4-ene-6-ol] trans-p-coumarate isolated from the birch buds was determined by NMR spectroscopy. The physico-chemical characteristics and NMR data of 6-hydroxyisocaryophyllene p-coumarate and others coumarates are demonstrated. The gas chromatographic retention indices of all identified compounds were determined. Birch buds contain derivatives of trans-coumaric acid. The antimicrobial activity of sesquiterpene alcohols coumarates was evaluated. The antimicrobial activity of sesquiterpene alcohols coumarates in relation to the following microorganisms: Escherichia coli, Proteus mirabilis, Staphylococcus aureus, Staphylococcus pneumonia and Klebsiella pneumonia was evaluated. The fraction of sesquiterpene alcohols coumarates showed activity against Staphylococcus epidermidis.